Evaluation of Suitability of Red Clay from Selected Areas of Gercus Formation, Sulaimaniyah, North Iraq, for the Construction of Embankment Dams - Hussain , Amera I. Hussain; Ibraheem, Ibraheem I. (Iraqi Journal of Science, 2021)
In this research, a geotechnical assessment was conducted for clay of the Gercus Formation to determine its suitability for embankment dams. The selected area is located in the north of Iraq. Six samples were collected from two sites in Dokan (Sulaimaniyah) and Haibat Sultan mountain (Koysinjaq), three samples each. Various geotechnical (physical, mechanical and chemical) tests were conducted based on standard specifications. The results of the grain size test of clay samples showed their conformity with Zone C curves and their suitability for the construction of embankment dams, according to the Iraqi standard for roads and bridges. The results of the plasticity limits test showed that the soil is made of fine, low plasticity silt (ML), and low plasticity clay (CL), according to the unified standard soil classification. The water content and plasticity limit tests (liquid limit, plastic limit, and plasticity index) demonstrated that these clays are conformable with the limits of the Iraqi standards. The results of the modified compaction test found a maximum dry density value of 1.962 g/cm3 with an optimum moisture content of 11.5%. The results of the permeability index (K) revealed low permeability according to the Das classification and, therefore, showed the suitability of the samples as raw filling materials in the construction of dams. Chemical tests (sulfate content, organic materials content, total dissolved salts, gypsum content, and pH value) showed compatibility with the requirements for the use in dams construction under the Iraqi standard (SoRB/ R5).